大学における一般体育受講者の共感性や社会的スキルの変化: スポーツチャンバラとグループフィットネスエクササイズを教材とした授業の比較 - 菅野, 慎太郎; 川井, 良介 (身体運動文化研究, 2024)
The purpose of this study was to examine how differences in disciplines in general physical education offered at universities cause changes in empathy and social skills of university students.Around 28 students attended the health and sports education course “Sports Education Practice （Sports Chanbara）” offered at Nihon University, College of Humanities and Sciences while another 28 attended “Sports Education Practice（Total Fitness）.” Of these, 20 students without deficiencies were selected as the study participants. They were administered the “Multidimensional Empathy Scale （MES）” and the “Social Skills Scale （hereafter, KiSS-18）” for the first time （pre）, 7th （mid）, and 15th（ post） classes. For the statistical analysis, two-way analysis of variance was used, with the class group （spochan group/fitness group） as the between-subjects factor and the time （pre/mid/post） as the within-subjects factor. Consequently, “imagination,” a factor that indicates a cognitive tendency to project oneself onto a fictional character was identified in the MES, and the improvement in the students was considerably higher after class in the spochan group. In addition, a main effect of the time factor was observed on the factor of “influence,” which indicates the tendency to be easily influenced by the feelings and opinions of others, and it showed higher values after the class than before it. In KiSS-18, effects were observed for all factors （basic skills, advanced skills, dealing-with-feeling skills, alternative-to-aggression skills, dealing-with-stress skills, and planning skills） in the time factor, and there was substantial improvement in these skills after the class.The findings revealed that social skills and empathy are improved by attending university physical education.